ROLE OF INTEGRATED RADIOLOGY INFORMATION SYSTEM FOR EMERGENCY RADIOLOGY - Efriza Nur Romadhoni; Darmini Darmini Darmini; Tri Andayani (Politeknik Kesehatan Kementerian Kesehatan Semarang, 2021)
Background: Emergency radiology has an important role. Based on several studies the factors responsible for delayed emergency care mostly involve imaging. All reports underscore the importance of imaging efficiency and the impact of imaging delays, which increase length of stay and exacerbate emergency department overcrowding, further limiting access to care and ultimately affecting radiographic results.Methods: This research is a qualitative research with a descriptive approach using literature study.Results:One of the problems in emergency services is waiting time as a local imaging barrier. A good RIS configuration is able to describe the workflow in each section, The digital imaging system supports the radiographer's records, including delays in the waiting room, and records of factors affecting scan time. HIS and RIS play a role in increasing patient efficiency and effectiveness. HIS stores, manages and captures information related to patient health activities and statistical data of health organizations. RIS is software that radiology installations use to improve radiological reporting quality and secure patient diagnostic results for years. As well as ensuring a smooth workflow in radiology installations and improving reporting quality.Conclusion: Good RIS integration is able to support the efficiency of emergency patient examinations, optimize patient waiting time and increase patient satisfaction.